Botanical composition of diets grazed by beef cows in the Kansas Flint Hills during winter - G.J. Eckerle; K. C. Olson; Walter H. Fick; L.A. Pacheco; John R. Jaeger (Kansas Agricultural Experiment Station Research Reports, 2010)
Analysis of microscopic plant fragments recovered from the gut of wild herbivores (i.e., microhistological analysis) has been used to estimate diet composition, but there is debate as to whether microhistological analysis of fecal samples is an appropriate method for characterizing diets of grazing beef cattle. Therefore, our goal was to determine whether this approach could effectively quantify the botanical composition of diets grazed by mature beef cows in the Kansas Flint Hills during winter.
Keywords: Cattlemen& #x27; s Day; 2010; Kansas Agricultural Experiment Station contribution; no. 10-170-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1029; Beef Cattle Research; 2010 is known as Cattlemen& #x27; s Day; Beef; Plants; Grazing; Botanical composition